A questionnaire study of parasite control in Thoroughbred and Standardbred horses in Australia. (7th February 2020) - Wilkes, Edwina J. A.; Heller, Jane; Raidal, Sharanne L.; Woodgate, Robert G.; Hughes, Kristopher J.
Abstract: Background: Information regarding parasite control practices currently used on Thoroughbred and Standardbred studs in Australia is lacking. Anthelmintic resistance (AR) is a global problem which has implications for equine health and welfare. Objectives: To identify parasite control practices currently used on horse studs in Australia and investigate the frequency of use of management factors that have been associated with the likelihood of promoting or delaying AR. Study design: Questionnaire study of equine parasite control on Thoroughbred and Standardbred studs in Australia. Methods: An online questionnaire was emailed to 300 studs in Australia. Information obtained included property details, grazing management, anthelmintic use, non‐chemotherapeutic parasite control practices, use of faecal egg counts (FECs) and perceptions of AR. Results: Seventy‐five completed questionnaires were received (25% response rate). Macrocyclic lactones (MLs) were the most commonly administered anthelmintics in mares and foals and less than 5% of respondents used targeted treatment regimens. The implementation of pasture hygiene practices was variable. The majority of respondents (97%) considered AR to be important; however, few respondents were aware of the use of FEC reduction tests for monitoring of drug efficacy. Main limitations: The potential for nonresponse bias was the main limitation of this study. Conclusions: Parasite control strategies on Australian stud farms remain over‐reliant on anthelmintic use. The frequent use of MLs is of concern for the increased selection pressure for AR. There is a lack of awareness of the importance of non‐chemotherapeutic strategies in integrated approaches to parasite control aimed at delaying the development of AR. This study highlights the need for greater veterinary involvement in the implementation of more sustainable parasite control practices with greater emphasis placed on surveillance through FEC testing.